2016
DOI: 10.3390/ijms17101598
|View full text |Cite|
|
Sign up to set email alerts
|

Decreased Expression of SRSF2 Splicing Factor Inhibits Apoptotic Pathways in Renal Cancer

Abstract: Serine and arginine rich splicing factor 2(SRSF2) belongs to the serine/arginine (SR)-rich family of proteins that regulate alternative splicing. Previous studies suggested that SRSF2 can contribute to carcinogenic processes. Clear cell renal cell carcinoma (ccRCC) is the most common subtype of kidney cancer, highly aggressive and difficult to treat, mainly due to resistance to apoptosis. In this study we hypothesized that SRSF2 contributes to the regulation of apoptosis in ccRCC. Using tissue samples obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Upstream sequence element (USE) in the 3'-UTR of BCL-w transcript contributed to 3'-end formation via interaction with splicing factors: U2 small nuclear RNA auxiliary factor 1 (U2AF35), U2 small nuclear RNA auxiliary factor 2 (U2AF65) and heterogeneous nuclear ribonucleoprotein I (hnRNPI) 52 . In addition, downregulation of serine and arginine-rich splicing factor 2 (SRSF2) was associated with decreased BCL-w transcript level 53 . It was also demonstrated that multiple copies in T-cell lymphoma-1 (MCT-1) protein Table 1.…”
Section: Regulation Of Bcl-w Levelmentioning
confidence: 99%
“…Upstream sequence element (USE) in the 3'-UTR of BCL-w transcript contributed to 3'-end formation via interaction with splicing factors: U2 small nuclear RNA auxiliary factor 1 (U2AF35), U2 small nuclear RNA auxiliary factor 2 (U2AF65) and heterogeneous nuclear ribonucleoprotein I (hnRNPI) 52 . In addition, downregulation of serine and arginine-rich splicing factor 2 (SRSF2) was associated with decreased BCL-w transcript level 53 . It was also demonstrated that multiple copies in T-cell lymphoma-1 (MCT-1) protein Table 1.…”
Section: Regulation Of Bcl-w Levelmentioning
confidence: 99%
“…Renal cell tumors represent a group of histopathologically and molecularly heterogeneous tumors, with different sets of genetic and epigenetic abnormalities [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. An increased understanding of the morphology, immunohistochemistry, genomics, and epidemiology of renal cell tumors has resulted in the identification of novel features in their molecular pathological epidemiology.…”
Section: Introductionmentioning
confidence: 99%
“…Renal cell carcinoma (RCC) represents a group of molecularly heterogeneous diseases characterized by differing sets of genetic and epigenetic abnormalities [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Microphthalmia-associated transcription (MiT) family translocation renal cell carcinoma (tRCC) is an RCC subtype characterized by early onset.…”
Section: Introductionmentioning
confidence: 99%